1997
DOI: 10.3346/jkms.1997.12.4.374
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal carcinosarcoma--a case report

Abstract: Carcinosarcoma of the adrenal gland is an extremely rare variant of adrenocortical carcinoma, characterized by a biphasic pattern of carcinoma and sarcoma-like components. We report a case of adrenal carcinosarcoma occurring in a 61-year-old Korean man who presented with right flank pain of one month duration radiating to the back and right iliac crest. The tumor measured 12 x 12 x 7 cm and adhered to the liver and right upper pole of the kidney. The carcinomatous component of the tumor showed polygonal cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…This adrenocortical carcinoma variant is extremely rare, and to our knowledge, only nine cases have been reported in the literature so far [3,8,9,10,16,24,30,33,38]. This tumor type is aggressive, and the recognition of diagnostic features of malignancy is not problematic.…”
Section: Sarcomatoid Carcinomamentioning
confidence: 99%
“…This adrenocortical carcinoma variant is extremely rare, and to our knowledge, only nine cases have been reported in the literature so far [3,8,9,10,16,24,30,33,38]. This tumor type is aggressive, and the recognition of diagnostic features of malignancy is not problematic.…”
Section: Sarcomatoid Carcinomamentioning
confidence: 99%
“…The first report of primary adrenal sarcomatoid carcinoma was in 1989 by Collina et al (6). At the time of writing the present study, to the best of our knowledge only 11 cases had previously been reported (6,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The majority of those patients succumbed to disease within a year, due to local recurrence or de novo metastases.…”
Section: Introductionmentioning
confidence: 59%
“…Data collected from the present patient, as well as from the previous 11 reported cases identified in the literature, revealed that the patient age range at the time of presentation with adrenal sarcomatoid carcinoma was 29-79 years, with a mean age of 55.75 years (6,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The female:male ratio in this small sample size was 1:1.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations